2018
DOI: 10.5056/jnm18050
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Distribution of the Gastrointestinal Tract Eosinophils in Childhood Functional Abdominal Pain Disorders

Abstract: Background/AimsAlthough functional abdominal pain disorders (FAPDs) are common in children, the accurate pathogenesis of FAPDs is not known yet. Micro-inflammation, particularly tissue eosinophilia of gastrointestinal (GI) tract, has been suggested as the pathophysiology observed in several GI disorders. We aimed to evaluate eosinophilic infiltration throughout the entire GI tract in children with FAPDs, compared to those with inflammatory bowel diseases (IBD) and to normal reference values.MethodsWe included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 46 publications
2
20
0
1
Order By: Relevance
“…IL-22BP levels in culture supernatants from normal and CD biopsies are consistent with the fact that eosinophils are the major source of IL-22BP in the gut. Indeed, higher levels of IL-22BP in the ileum compared to the colon is consistent with the known intestinal distribution of eosinophils 44,[51][52][53] and IL-22BP levels ae weakly but significantly correlated with eotaxins ones 44 . We found no correlation between TNF and IL-22BP as shown by Pelczar et al at the mRNA level 32 , suggesting that IL-22BP levels are not modulated by the state of inflammation.…”
Section: Discussionsupporting
confidence: 83%
“…IL-22BP levels in culture supernatants from normal and CD biopsies are consistent with the fact that eosinophils are the major source of IL-22BP in the gut. Indeed, higher levels of IL-22BP in the ileum compared to the colon is consistent with the known intestinal distribution of eosinophils 44,[51][52][53] and IL-22BP levels ae weakly but significantly correlated with eotaxins ones 44 . We found no correlation between TNF and IL-22BP as shown by Pelczar et al at the mRNA level 32 , suggesting that IL-22BP levels are not modulated by the state of inflammation.…”
Section: Discussionsupporting
confidence: 83%
“…With regard to the eosinophilic infiltration of different parts of the gastric mucosa, the reports are conflicting. Some studies have shown no differences in the eosinophilic infiltration of the gastric antrum compared to the gastric body [ 3 ], while others reported a greater eosinophilic infiltration of the gastric antrum (but not of the gastric body) in children with functional abdominal pain disorders compared to healthy controls [ 6 ]. The differences in eosinophilic counts found between the different parts of the stomach in our study were not related to the presence or not of abdominal pain, but may be considered in the context of the geographical variations that we found in all of the GI biopsies, a finding consistent with previous reports on eos concentrations in normal colonic mucosa [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the eosinophilic density of GI tract mucosa of healthy children, which would provide baseline data for the diagnosis of EGIDs, has been poorly defined [ 2 - 5 ]. Inflammatory bowel disease has been reported to be associated with increased eosinophilic infiltration of the childhood GI tract [ 6 ], while the association of functional GI disorders (FGIDs) with increased eosinophil (eos) density of the child’s GI tract is controversial: some studies report increased eosinophilic infiltration of the GI tissue mucosa in children with FGIDs [ 7 ], whereas others do not [ 8 ]. Furthermore, the geographical variations in the distribution or density of GI tissue eos in children with no organic diseases have been poorly defined.…”
Section: Introductionmentioning
confidence: 99%
“…All denied a history of abdominal pain, constipation, or diarrhea. We did not sex or age-match controls as colonic cell density does not appear to be affected by sex or age in children 49 51 .…”
Section: Methodsmentioning
confidence: 99%